CGA restrains the apoptosis of Aβ25-35-induced hippocampal neurons. (2nd July 2020) - Shi, Min; Sun, Fan; Wang, Yanbo; Kang, Junling; Zhang, Shuqing; Li, Hongfu
Abstract: Background: Chlorogenic acid (CGA) has anti-oxidant and anti-inflammatory effects, but the study on its role in Alzheimer's disease (AD) models remains rare. Here, the effects of CGA on β-amyloid protein (Aβ)-induced cell models were investigated, aiming to provide a direction for Aβ-induced AD. Material and methods: Hippocampal neurons were separated from newborn Sprague-Dawley (SD) rats and identified by immumofluorescence method. Hippocampal neurons were processed with Aβ25-35 after pre-treatment CGA. MTT assay was used for detecting viability of treated cells. The activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), malondialdehyde (MDA) and lactate dehydrogenase (LDH) of treated hippocampal neurons were determined by corresponding kits. Flow cytometry analysis assessed the apoptosis and mitochondrial membrane potential (MMP) in hippocampal neurons after treatment. The expressions of proteins related to apoptosis and endoplasmic reticulum stress (ERS) were measured by western blot (WB) analysis. Results: Immumofluorescence method showed that the Aβ25-35 induction models were successfully constructed. CGA increased the viability and decreased the apoptosis rate of Aβ25-35 -induced hippocampal neurons. Decreasing activities of LDH and MDA, and raised contents of SOD and GSH-Px were appeared in Aβ25-35 -induced cells that pre-treated with CGA. Moreover, CGA also enhanced MMP intensity of hippocampal neurons induced by Aβ25-35 . In WB analysis, CGA reversed the promoting effect of Aβ25-35 on the expressions of proteins related to pro-ERS and pro-apoptosis. Conclusion: CGA restrained the apoptosis of Aβ25-35 -induced hippocampal neurons via improving the anti-oxidant capacity, mitochondrial injury and ERS state of cells, which may provide a direction for AD.